2018
DOI: 10.1071/sh17110
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Chlamydia trachomatis, Neisseria gonorrhoeae, Trichomonas vaginalis and Mycoplasma genitalium: an observational study of testing patterns, prevalence and co-infection rates in northern New Zealand

Abstract: There are disparately low testing rates for STIs in certain high-risk groups in northern New Zealand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 14 publications
3
17
0
Order By: Relevance
“…Recent studies have revealed that inadequate antibiotic coverage against the associated bacteria in chlamydial cervicitis is one of the most prevalent causes of the failure of the treatment. Additionally, some studies indicated that mycoplasma genitalium is one of the most common bacteria associated with chlamydia trachomatis, and moxifloxacin is one of the most effective drugs for the treatment of mycoplasma genitalium (21)(22)(23)(24)48). Based on the reports of some studies, mycoplasma genitalium treatment failed with macrolides such as azithromycin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have revealed that inadequate antibiotic coverage against the associated bacteria in chlamydial cervicitis is one of the most prevalent causes of the failure of the treatment. Additionally, some studies indicated that mycoplasma genitalium is one of the most common bacteria associated with chlamydia trachomatis, and moxifloxacin is one of the most effective drugs for the treatment of mycoplasma genitalium (21)(22)(23)(24)48). Based on the reports of some studies, mycoplasma genitalium treatment failed with macrolides such as azithromycin.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have also reported azithromycin treatment failure (18)(19)(20)(21)(22)(23)(24). In trying to reduce these failures, diagnostic advances are made in relation to chlamydial cervicitis.…”
mentioning
confidence: 99%
“…Trials comparing azithromycin with doxycycline or other medications for the treatment of Chlamydiatrachomatis in women (cervicitis, urethritis, and rectal infection) or men (urethritis and rectal infection) were assessed. The inclusion criteria were: (1) Being a randomized clinical trial or a clinical trial; (2) Comparing treatment regimens of oral azithromycin (single- or multiple-dose regimens) with oral doxycycline (twice daily 100░mg for seven days) or other regimens; (3) Being a man or woman over the age of 12; (4) Assessment of microbial or clinical recovery during a follow-up period of 1–9 wk; and (5) Reporting treatment failure during the trial.…”
Section: Methodsmentioning
confidence: 99%
“…Chlamydia is one of the most common Sexually Transmitted Diseases (STDs) in the world, which has a higher prevalence among adolescents and women (1). According to the latest World Health Organization (WHO) reports, the reported prevalence of chlamydia has steadily increased over the last two decades, and 92 million new cases of chlamydia trachomatis infection occurred in 2009, reaching 101, 131, and 153 million in 2011, 2012, and 2015, respectively (2,3). The risk factors for chlamydial infection include age 15–24, several sexual partners, unprotected sex, and previous history of STDs.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed, among multiple infections, dual infection with CT and MG was the most commonly observed in northern New Zealand. 36 Informing educational and behavioral approaches to STI interventions There are three effective approaches for disease control: education and behavioral changes, screening for and treatment of asymptomatic disease, and diagnosis and treatment of symptomatic disease. 9 Controlling STIs is dependent not only on case detection and appropriate treatment, but also screening and treatment of asymptomatic disease to prevent complications and further spread of infection in the community.…”
Section: Expanding Screening Of Stis For Larger Segments Of the Populmentioning
confidence: 99%